Setting the 'right' goal: Post M&A innovation performance and goal orientation - Doan Thu Trang (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Pharmaceutical firms spend billions of dollars to develop the next breakthrough drug and to maintain their market shares. We investigate how pharmaceutical firms use mergers and acquisitions to boost their innovation performance which has been found to result in better performance outcomes. Adding to the recent research on mergers and acquisitions, we found that firms that are explicit with their R&D goal orientation from the beginning of the acquisition journey are more successful in their innovation endeavours than firms with other goal orientation. Further, the firms' prior acquisition experience appears to aid their innovation performance. However, we found that target size can affect the post-acquisition innovation performance but has diminishing returns as target size increases. Ultimately, our findings suggest that having an explicit R&D goal orientation is really important for a healthy innovation pipeline for pharmaceutical firms.
Keywords: L25; L65; O32; 650; mergers and acquisitions; innovation; R&D; goal orientation; acquisition experience; organizational learning; pharmaceutical industry